Financial Management Knowledge, Human Resource Capability, Information Technology Utilization, and Income among Women-Owned MSMEs - Reni Dwi Widyastuti; Ali Afif; Sartono Sartono (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Women-owned MSMEs are important to local economic inclusion but may face gaps in financial capability, human resource capability, and digital utilization. Objective: This study aims to analyze the influence of financial management, human resource capability (HR) and information technology on income of Women's MSMEs in Kubu Raya Regency. Methods: The population of this study were women MSMEs in Kubu Raya Regency. The sample of this study amounted to 120 female MSME players, with the technique of collecting sample data using purposive sampling. Data analysis was carried out using multiple regression techniques to test the research hypothesis. This research uses a quantitative approach with SPSS test tools. Results: The results of this study indicate that financial management knowledge, human resource capabilities and utilization of information technology partially and simultaneously have a significant effect on the income of Women's MSMEs in Kubu Raya Regency. Conclusion: Internal capabilities and technology utilization are relevant correlates of the measured income score, but cross-sectional self-reported data do not establish causality.